2000
DOI: 10.1007/s005350050022
|View full text |Cite
|
Sign up to set email alerts
|

Changes of liver fibrosis in chronic hepatitis C patients with no response to interferon-α therapy: including quantitative assessment by a morphometric method

Abstract: The aim of this study was to evaluate the antifibrotic effect of interferon (IFN)-alpha in chronic hepatitis C (CH-C) patients with no response to IFN-alpha therapy. We studied 76 patients (46 men, 30 women; mean age, 55.6 years) who received IFN-alpha intramuscularly, at a total close of 480 to 880MU for 6 months (group A). As a control group, we studied 50 patients (32 men and 18 women; mean age, 58.5 years) with CH-C who received medication other than IFN (ie, Strong-Neo-Minophagen C, ursodeoxycholic acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
0
20
2
Order By: Relevance
“…Sho-saiko-to has been used for the treatment of various infectious diseases such as chronic viral hepatitis, [1][2][3] and it has been shown that Sho-saiko-to has immunomodulating activity, [4][5][6][7][8] antiinflammatory effects, [9][10][11] and antihepatitis activity. [12][13][14] Previously, we demonstrated that the immunomodulating actions of Sho-saiko-to, such as augmentation of macrophage function and mitogenic activity, were mainly due to its polysaccharide fractions in vivo.…”
mentioning
confidence: 99%
“…Sho-saiko-to has been used for the treatment of various infectious diseases such as chronic viral hepatitis, [1][2][3] and it has been shown that Sho-saiko-to has immunomodulating activity, [4][5][6][7][8] antiinflammatory effects, [9][10][11] and antihepatitis activity. [12][13][14] Previously, we demonstrated that the immunomodulating actions of Sho-saiko-to, such as augmentation of macrophage function and mitogenic activity, were mainly due to its polysaccharide fractions in vivo.…”
mentioning
confidence: 99%
“…Indeed, it has been shown by some authors that even in nonresponding patients HCV-related cirrhosis progression may be lowered by IFN therapy. 23,24 Further studies should be done to assess the possibility of a benefi cial effect of PEG-IFN standard treatment in nonresponders and even of low-dose, long-term therapy. Combination treatment with PEG IFN alpha-2a and ribavirin is hampered by the augmented risk of severe anemia in this category of patients.…”
Section: Discussionmentioning
confidence: 99%
“…We examined whether hepatic INF-a expression could improve liver fibrosis in a DMN-injected rat, because the antifibrotic effect of IFN-a protein has been shown in experimental animal models and clinical studies. [6][7][8][9][10][11][12][13] The AxCA-rIFN-treated rats survived significantly longer than the rats injected with either AxCA-lacZ or PBS (P¼0.0001), and five of nine IFN-a-transduced rats survived more than 100 days ( Figure 3). Histological examination clearly revealed less fibrous connective tissue components in Glisson's sheath and pseudolobule formations in the livers of control and AxCA-rIFNtransduced rats than in the liver of the AxCA-lacZtransduced rats, in which the extensive formation of fibrotic septa and thickened reticulin fibers joining central areas were observed (Figures 1a, 4a and b).…”
Section: Intravenous Adenovirus Vector Injection Into Rats With Dmn-imentioning
confidence: 99%
“…In addition to the antiviral effect, several lines of evidence suggested that IFN-a is also effective in curtailing LC in experimental animal models and clinical studies. [6][7][8][9][10][11][12][13] IFN-a is therefore expected to be particularly powerful in preventing the development of LC in patients with HCV infection.…”
Section: Introductionmentioning
confidence: 99%